Pelaksanaan Pembelajaran Daring PJOK pada Masa Pandemi Covid-19 di SMP Se-Kecamatan Dempet Kabupaten Demak Tahun Pelajaran 2020/2021 - Agus Miftah; Agus Pujianto; Dwi Tiga Putri (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the implementation of PJOK online learning during the COVID-19 pandemic in junior high schools throughout the Dempet District, Demak Regency, for the 2020/2021 academic year, including planning, implementing and evaluating learning. This study used a qualitative research with a descriptive approach, with data sources taken from 6 principals, 8 PJOK teachers and 36 students, 6 students from each school were taken as samples. The result of the research is that most of the teachers have made learning plans according to distance learning. The implementation of PJOK learning is carried out in 2 ways, namely the online method using WhatsApp media and google forms, and the blended learning method by dividing by half the number of students in each class for face-to-face and online, for online using WhatsApp. Evaluation has been carried out through three aspects, namely affective, cognitive and psychomotor. In conclusion, the implementation of PJOK online learning during the COVID-19 pandemic in junior high schools throughout the Dempet District, Demak Regency, for the 2020/2021 academic year is quite good.